Transmitters and Receivers for High Capacity Indoor Optical Wireless Communication - Mikolaj Wolny; Eduardo Muller; Eduward Tangdiongga (Telecom)
In this paper, we present recent advancements in transmitter and receiver technologies for Optical Wireless Communication (OWC). OWC offers very wide license-free optical spectrum which enables very high capacity transmission. Additionally, beam-steered OWC is more power-efficient and more secure due to low divergence of light. One of the main challenges of OWC is wide angle transmission and reception because law of conservation of etendue restricts maximization of both aperture and field of view (FoV). On the transmitter side, we use Micro Electro-Mechanical System cantilevers activated by piezoelectric actuators together with silicon micro-lenses for narrow laser beam steering. Such design allowed us to experimentally demonstrate at least 10 Gbps transmission over 100° full angle FoV. On the receiver side, we show the use of photodiode array, and Indium-Phosphide Membrane on Silicon (IMOS) Photonic Integrated Circuit (PIC) with surface grating coupler (SGC) and array of SGC. We demonstrate FoV greater than 32° and 16 Gbps reception with photodiode array. PIC receiver allowed to receive 100 Gbps WDM with single SGC, and 10 Gbps with an array of SGC which had 8° FoV in the vertical angle and full FoV in the horizontal angle. Our results suggest that solutions presented here are scalable in throughputs and can be adopted for future indoor high-capacity OWC systems.